Disturbance in Maternal Environment Leads to Abnormal Synaptic Instability During Neuronal Circuitry Development - Hatanaka, Yusuke; Tomohiro, Kabuta; Wada, Keiji (Frontiers in Neuroscience, 2017)
Adverse maternal environment during gestation and lactation can have negative effects on the developing brain that persist into adulthood and result in behavioral impairment. Recent studies of human and animal models suggest epidemiological and experimental association between disturbances in maternal environments during brain development and the occurrence of neuropsychiatric disorders, including autism spectrum disorder, attention deficit hyperactivity disorder, schizophrenia, anxiety, depression, and neurodegenerative diseases. In this review, we summarize recent advances in understanding the effects of maternal metabolic and hormonal abnormalities on the developing brain by focusing on the dynamics of dendritic spine, an excitatory postsynaptic structure. We discuss the abnormal instability of dendritic spines that is common to developmental disorders and neurological diseases. We also introduce our recent studies that demonstrate how maternal obesity and hyperandrogenism leads to abnormal development of neuronal circuitry and persistent synaptic instability, which results in the loss of synapses. The aim of this review is to highlight the links between abnormal maternal environment, behavioral impairment in offspring, and the dendiric spine pathology of neuropsychiatric disorders.